Some Advances in Electric Rocket Propulsion for Space Exploration - B. Abbasov, Iftikhar; M, Nosrati (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2025)
This article examines some of the current challenges facing electric propulsion designers to improve space exploration efficiency. The paper discusses various types of electric motors, such as ion, plasma engines, and compares their performance characteristics. The importance of using electric engines for interplanetary missions and reducing the costs of space exploration is noted. The problems and limitations of electric motors are also described, and new technologies that can solve these problems are noted. The use of nanotechnology to develop lightweight, high-performance propulsion materials could contribute to the longevity of plasma thrusters. As a result, it is concluded that electric propulsion systems have a large reserve in the field of advancing space missions.